The concept of smart cities: a sustainability aspect for future urban development based on different cities - Addas, Abdullah (Frontiers in Environmental Science, 2023)
To meet resident's needs, the scientists suggest the concept of smart cities for urban transformation. Urban green spaces (UGSs) are designed to investigate improving lifestyles. Environmental performance on a global scale is becoming challenging due to climatic changes and rapid advancement. To remedy the issues, the establishment of highly sustainable and healthier ecosystems is a crucial demand, having an emphasis on the design of smart cities by preventing disease and addressing the basics of living quality. Urban populations are increasing enormously, a strong obstacle to developing a pollution-free environment. The research deals with cities' current developments, especially smart cities' sustainability, which is required to meet the current demands. In addition to the developments, the ranking of different cities is compared utilizing city rankings. To explain the climate-related goals, both national and international objectives and the legal framework are considered. The work compares the cities of Vienna, Copenhagen, Amsterdam and Hamburg. The comparison is based on the four categories of land distribution and use, mobility and transport, building standards and supply and disposal. Due to the high standard of living and its leading position in various rankings, special attention was paid to the City of Vienna. The work is well developed with various component components of sustainability and future development to enhance the quality of life and minimize air pollution. Finally, the problems and improvement possibilities of the cities are discussed. The work aims to look at the sustainability goals and projects that could be important in an ecological and sustainable city in the future. The comparison study of different cities shows smart cities' importance and their effect on health.